Human P301L-mutant tau expression in mouse entorhinal-hippocampal network causes tau aggregation and presynaptic pathology but no cognitive deficits. - Julie A Harris; Akihiko Koyama; Sumihiro Maeda; Kaitlyn Ho; Nino Devidze; Dena B Dubal; Gui-Qiu Yu; Eliezer Masliah; Lennart Mucke (PLoS ONE, 2012)
Accumulation of hyperphosphorylated tau in the entorhinal cortex (EC) is one of the earliest pathological hallmarks in patients with Alzheimer's disease (AD). It can occur before significant Aβ deposition and appears to "spread" into anatomically connected brain regions. To determine whether this early-stage pathology is sufficient to cause disease progression and cognitive decline in experimental models, we overexpressed mutant human tau (hTauP301L) predominantly in layer II/III neurons of the mouse EC. Cognitive functions remained normal in mice at 4, 8, 12 and 16 months of age, despite early and extensive tau accumulation in the EC. Perforant path (PP) axon terminals within the dentate gyrus (DG) contained abnormal conformations of tau even in young EC-hTau mice, and phosphorylated tau increased with age in both the EC and PP. In old mice, ultrastructural alterations in presynaptic terminals were observed at PP-to-granule cell synapses. Phosphorylated tau was more abundant in presynaptic than postsynaptic elements. Human and pathological tau was also detected within hippocampal neurons of this mouse model. Thus, hTauP301L accumulation predominantly in the EC and related presynaptic pathology in hippocampal circuits was not sufficient to cause robust cognitive deficits within the age range analyzed here.